2016
DOI: 10.1039/c6ob00248j
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric nucleophilic dearomatization of diazarenes by anion-binding catalysis

Abstract: The first anion-binding organocatalyzed enantioselective Reissert-type dearomatization of diazarenes has been developed. This reaction represents a synthetic challenge since diazarenes have various reactive sites. The use of a chiral tetrakistriazole as a C-H-based hydrogen-donor catalyst allowed the straightforward highly regio- and enantioselective synthesis of a variety of chiral diazaheterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Due to the chirality of the catalyst, only one hand of the helix is observed, giving impressive enantiomeric ratios of up to 98 : 2 in the final product. The same group have subsequently synthesised related chiral foldamers and shown that they can act as enantioselective catalysts for the dearomatization of pyridines, [37] isoquinolines, [38] and diazarenes [39] …”
Section: Foldamersmentioning
confidence: 99%
“…Due to the chirality of the catalyst, only one hand of the helix is observed, giving impressive enantiomeric ratios of up to 98 : 2 in the final product. The same group have subsequently synthesised related chiral foldamers and shown that they can act as enantioselective catalysts for the dearomatization of pyridines, [37] isoquinolines, [38] and diazarenes [39] …”
Section: Foldamersmentioning
confidence: 99%
“…A good regioselectivity of 95:5 was obtained in favor of the C-2-addition product 127 when 2,2,2-trichloroethyl chloroformate (trocCl) was used in the presence of methyl tert -butyl ether (MBTE) ( Scheme 52 ). After the separation from the minor 4-addition product 128 , the 2-addition compound 127 was obtained in 86% yield and a good 83:17 enantiomeric ratio [ 88 ].…”
Section: Reactivity Of 15-naphthyridinesmentioning
confidence: 99%
“…Following the aforementioned studies, the Mancheno group designed and synthesized various chiral triazole-based complexes such as L2–L4 (Scheme 2) [3639]. It was proposed that while these triazole derivatives are conformationally flexible, upon their binding to halogen anions these complexes adopt a reinforced chiral helical conformation.…”
Section: Reviewmentioning
confidence: 99%
“…Application of chiral triazole-based catalysts L3 and L4 for counterion activation of pyridinium, quinolinium and isoquinolinium salts by Mancheno and co-workers [3639]. …”
Section: Reviewmentioning
confidence: 99%